Usefulness of excimer laser in acute coronary syndrome with left main coronary artery: a case series. Issue 6 (1st December 2020) - Imaoka, Takuro; Takagi, Kensuke; Morita, Yasuhiro; Kanzaki, Yasunori; Nagai, Hiroaki; Watanabe, Naoki; Tsuboi, Hideyuki; Morishima, Itsuro
Abstract: Background: Acute coronary syndrome caused by unprotected left main coronary artery (ACS-ULMCA) occlusion has a high mortality due to the formation of plaques and rich thrombi. Although excimer laser coronary angioplasty (ELCA) is effective in debulking and ablation of plaque burden and rich thrombi, its effectiveness in ACS-ULMCA remains unknown. Case summary: We conducted percutaneous coronary intervention (PCI) using ELCA for six patients with ACS-ULMCA from February 2016 to May 2019. This case series includes a 65-year-old man who presented with sudden-onset chest pain. Angiography revealed subtotal occlusion of the left main coronary artery (LMCA). The use of a 0.9-mm ELCA catheter advanced from LMCA to the left anterior descending artery markedly improved coronary blood flow, and intravascular ultrasound revealed debulking of the plaque and thrombus. Another 79-year-old man presented with chest pain. Angiography revealed total occlusion of LMCA. Use of a 0.9-mm ELCA catheter improved coronary blood flow. Subsequent kissing balloon technique led to satisfactory results. All cases needed mechanical support (such as intra-aortic balloon pumping or percutaneous cardiopulmonary support) prior to PCI. Five patients survived finally, and one died 34 days after primary PCI. Discussion: After stabilizing haemodynamics by mechanical support, ELCA could be a good option to improve coronary blood flow in patients with ACS-ULMCA.